DEVELOPMENT OF STUDENTS' CREATIVE ABILITIES THROUGH TEACHING LANDSCAPING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the development of students' creative abilities in the process of landscape painting. The study examines the importance of developing creative thinking, aesthetic perception, and emotional expression skills through art education. Teaching landscape painting significantly increases students' creative abilities, especially in the development of visual thinking and skills for creative problem-solving. The article concludes with recommendations for optimizing art education programs.